2022
DOI: 10.26434/chemrxiv-2022-prv2w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing the local environment of active sites during 2-propanol oxidation to acetone on the Co3O4 (001) surface: insights from first principles O K-edge XANES spectroscopy

Abstract: We use theoretical X-ray absorption near-edge spectroscopy (XANES) to investigate the electronic structure of the active sites during 2-propanol oxidation to acetone on the Co3O4 (001) surface in humid conditions. In the gas phase, the O K-edge spectra of 2-propanol and acetone as well that of 2-propoxide considered as reaction intermediate, present no pre-edge peaks. Upon 2-propanol adsorption at the Co site of Co3O4 (001) surface, the O K-edge spectrum presents a distinct peak preceded by a bumb in the pre-e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…9,10 In such processes, water can play a controversial role as it could destabilize [11][12] or stabilize co-adsorbed species. [13][14][15] However, compared to the (001) and (101) that were studied at different coverage regimes, [16][17][18][19] the interaction of water with the Co3O4 (111) has not been studied to an extend that would allow a fundamental understanding of its role on the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In such processes, water can play a controversial role as it could destabilize [11][12] or stabilize co-adsorbed species. [13][14][15] However, compared to the (001) and (101) that were studied at different coverage regimes, [16][17][18][19] the interaction of water with the Co3O4 (111) has not been studied to an extend that would allow a fundamental understanding of its role on the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In addition, the various electronic, magnetic and redox properties of Co 3 O 4 have also stimulated several studies in recent years. [10][11][12][13][14][15] Falk et al 1 studied the oxidation of 2-propanol over Co 1+x Fe 2-x O 4 spinel oxides in contact with both the liquid and the gas phase. They reported that increasing the Co content will increase the catalytic activity of the samples for 2-propanol oxidation, which shows that the iron-free Co 3 O 4 samples have the highest catalytic activity.…”
Section: Introductionmentioning
confidence: 99%